Computer-aided design of a tensegrity structure. (April 2022) - Botis, Marius Florin; Imre, Lajos; Cerbu, Camelia
Highlights: Conformation of the tensegrity structure based on the iterative numerical method. Flow chart of the work method used in the process of the structural conformation. Validation of the numerical method for conformation of tensegrity structure by experiment. Validation of the numerical method for conformation of structures by analytical method. Using the method proposed for the tensegrity superstructure of a civil structure. Abstract: In recent years, the integration of tenstegrity structures in the field of civil engineering has taken off, as the difficulties of execution have been overcome. Because the literature is poor in publications related to the computer-aided design methods used to conform the tensegrity structures, the main objectives of this research are: (i) analytical and experimental validation of the numerical method used in structural conformation; (ii) conformation of the tensegrity structure based on the incremental-iterative numerical method; (iii) obtaining of a novel tensegrity structure. Firstly, some theoretical aspects regarding the problem of solving a structure and the stability of the tensegrity structures are presented. It is shown the flow chart of the work method used in the process of the structural conformation. The numerical method is firstly validated by analytical method applied in case of the two-dimensional structure with elastic support, developed by M. A. Crisfield. Additionally, the equilibrium force–displacement curves obtained by measuring the displacements of a node of a three-dimensional tensegrity structure on the force direction, related to the incremental forces, are compared with the ones obtained by numerical method. The average value of the errors is equal to 3.128% by comparing the displacements recorded by experimental and numerical methods. The novel superstructure of a civil building, based on a two-dimensional polygonal tensegrity structure expanded in space, is step-by-step conformated by using the computer-aided design method proposed in this paper.